Republic of Moldova Forest Policy Note - World Bank (Washington, DC, 2015)
This forest policy note (FPN) offers an outside view of the Moldovan forestry sector, provides some strategic guidance to help define sector goals, and identifies opportunities for consideration in the continued development of the sector and for the implementation of the Moldova and World Bank (WB) country partnership strategy (CPS). This study is based on a number of short visits to Moldova and on a number of background studies undertaken during the implementation of both phases of the European neighborhood and partnership instrument (ENPI) east countries, forest law enforcement and governance (FLEG) program. The WB CPS for Moldova recognizes that the forestry sector plays an important role for competitiveness and climate change but has not received the attention it deserves. This FPN builds on previous work within the forestry sector. It aims to inform the WB project formulation process and the forestry sector by reviewing the sector and highlighting the main policy issues and identifying possible actions.